2023
DOI: 10.1002/mnfr.202300378
|View full text |Cite
|
Sign up to set email alerts
|

The Dose‐Dependent Effect of Curcumin Supplementation on Inflammatory Response and Gut Microbiota Profile in High‐Fat Fed C57BL/6 Mice

Caroline Bertoncini‐Silva,
Priscila Giacomo Fassini,
Daniela Carlos
et al.

Abstract: ScopeThe prevalence of obesity has increased, with excessive consumption of high‐fat foods being one of the primary causes. Curcumin, a polyphenol extracted from Curcuma longa L., exhibits anti‐inflammatory activity.  The study aims to investigate the effects of curcumin supplementation in different doses on the biochemical profile, inflammatory response, and gut microbiota profile in mice that are fed with high‐fat diet (HFD).Methods and resultsC57BL/6 male mice are fed a standard diet, or a HFD with or witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Bertoncini-Silva et al studied C57BL/6 male mice fed a HFD with different doses of curcumin (50, 250, and 500 mg/kg body weight), and they observed that, in the liver, there was a reduction in TNF-α at all three doses and an increase in IL-10 at doses of 50 and 250 mg/kg body weight [ 130 ].…”
Section: Curcumin and Curcuminoidsmentioning
confidence: 99%
“…Bertoncini-Silva et al studied C57BL/6 male mice fed a HFD with different doses of curcumin (50, 250, and 500 mg/kg body weight), and they observed that, in the liver, there was a reduction in TNF-α at all three doses and an increase in IL-10 at doses of 50 and 250 mg/kg body weight [ 130 ].…”
Section: Curcumin and Curcuminoidsmentioning
confidence: 99%
“…Astragalus polysaccharides , the main effective component of Astragalus mongholicus Bunge, significantly regulated most microorganisms, such as Bifidobacterium pseudolongum , Lactobacillus johnsonii and Lactobacillus , the changes in abundance of these microorganisms were related to the increase of metabolites, which could control tumor growth ( Ding et al, 2021 ). The main active ingredients of Curcuma aromatica Salisb., curcumin showed the dose-dependent suppressive effect on inflammatory response and gut microbiota profile in high-fat fed C57BL/6 mice ( Bertoncini-Silva et al, 2023 ). The intricate mechanisms supporting this therapeutic effect, however, still need to be clarified.…”
Section: Introductionmentioning
confidence: 99%